ORIENTASI FOTOGRAFI PENGUNJUNG ANJUNGAN WISATA DI KAWASAN MANGUNAN: KAJIAN FUNGSI FOTO POTRET DI MEDIA SOSIAL INSTAGRAM - Pitri Ermawati (Specta: Journal of Photography, Arts, and Media, 2018)
Abstrak Penelitian ini bermaksud menjelaskan orientasi fotografi pengunjung yang berfoto di anjungan wisata kawasan Mangunan dengan objek penelitian berupa foto potret di media sosial Instagram. Menerapkan metode penelitian deskriptif-kualitatif, analisis kritis dilakukan dalam pembacaan foto-foto potret menggunakan telaah fungsi foto potret Soeprapto Soedjono, serta telaah aspek teknis-fisik fotografi potret yang dikemukakan oleh Famous Photographers School. Mengambil sampel berupa lima foto dari lima akun Instagram yang berlatar di lima anjungan wisata di kawasan Mangunan, hasil penelitian menunjukkan tiga fungsi foto potret yang diunggah oleh para pengunjung yang merupakan subjek foto sekaligus pemilik akun Instagram; yaitu fungsi personal, sosial, dan komersial. Dalam upaya mewujudkan foto potret yang sesuai dengan fungsi-fungsi tersebut, pengunjung tampak memperhitungkan aspek teknis-fisik fotografi potret berupa pencahayaan, pose, dan background. Adapun poperti, kurang mendapatkan perhatian dikarenakan tidak semua anjungan menyediakannya. Kata kunci: fotografi, anjungan, foto potret, Instagram   AbstractVisitors’ Photography Orientation of Scenery Stages in Mangunan Tourism Area: Study of The Functions of Portrait Photos in Social Media Instagram. This research explains the photography orientation of visitors who taking photograph of theirselves (portrait) on the scenary stages (selfie spots) in Mangunan tourism area, by studying their portraits in social media Instagram. This research allows the descriptive-qualitative method. It uses the study of the portrait  functions explained by Soeprapto Soedjono to read and to analise the portrait photos. It also studies the physical-technical aspect in portrait photography explained by Famous Photographers School applied by the visitors. There are five portrait photo samples from five Instagram accounts which setting are on scenery stages in Mangunan tourism area. This research conclusion shows three functions of the portrait photos uploaded by the visitors, either as the Instagram account owners and the subjects (sitters) of those photos: personal function, social function, and commercial function. In order to make her/ his portrait matches on the function desired, visitor seems to care about physical-technical aspects on portrait photography: lighting, pose, and background. Another element is property, which is the most ignorable element due to it’s rare availability on the spot.   Keywords: photography, scenary stage, portrait photo, Instagram